STUDI APOLOGETIK KRISTEN TERHADAP KONSEP ANAK ALLAH YANG DITERAPKAN PADA PRIBADI YESUS KRISTUS - Esap Veri (SEKOLAH TINGGI TEOLOGI KIBAID, 2021)
In this satudy the author discusses the concept of the Son of God which is applied to the person of Jesus Christ in the study of Apologetics. This topic is controversial because it often distors theological understanding as if the Christian faith teaches that God has biological children and this creates a theological misunderstanding. This sometimes understood by non-Christian.Therefore, the author will use the study of literature in research in order to explain the phenomenon under study.This study shows that the concept of the Son of God is not a concept that means the biological son of God. But the concept of the son of God is a concept that has meaning: first, Jesus is equal to God the Father. Second, Jesus Christ is the unique Son of God as well as having a personal relationship with the Father, so that it is the Son who reveals the entire existence of the Father. who has uniquely revealed the exixtence of the Father.